National survey to evaluate musuloskeletal health in retired professional ballet dancers in the United Kingdom. (January 2017) - Smith, T.O.; de Medici, A.; Oduoza, U.; Hakim, A.; Paton, B.; Retter, G.; Haddad, F.S.; Macgregor, A.
Abstract: Objectives: To explore the musculoskeletal health of retired professional ballet dancers in the United Kingdom (UK). Design: Online national survey. Participants: Retired professional ballet dancers living in the UK. Methods: The survey explored: what musculoskeletal injuries or diseases are experienced by retired professional ballet dancers; which anatomical regions were affected by musculoskeletal injuries or diseases in retired professional ballet dancers; whether ballet dancers were forced to retire from professional ballet due to musculoskeletal injuries or disease. Results: Forty-six retired ballet dancers responded. Thirty-six percent (n = 17) of respondents reported retiring from ballet due to musculoskeletal injury. The median age when respondents retired from professional ballet was 29 years. The most common issues that caused people to retire were hip and back pain (25%; n = 9 respectively), followed by hamstring injuries, ankle injuries, cervical spine injuries, and anterior knee pain (13% respectively; n = 5). Ninety-one percent (n = 42) reported experiencing muscle and joint pain post-retirement. Conclusions: Musculoskeletal pain and disease was a problem for respondents in this study. Further investigation is needed to define the problem, so management can be examined. Comparing performance and training regimes to injury rates in professional dancers, and then following these cohorts into retirement, would increase knowledge on this population. Highlights: Musculoskeletal disorders are a challenge for retired professional ballet dancers. 91% of this study's cohort have experienced musculoskeletal pain and symptoms. 36% of this cohort retired from professional ballet due to musculoskeletal injury. Common anatomical regions affected include the lumbar spine, knee, hip and neck.